PENINGKATAN KEMAMPUAN GURU PAH DALAM MEMANFAATKAN LINGKUNGAN SEKOLAH SEBAGAI SUMBER BELAJAR MELALUI DISKUSI KELOMPOK KERJA GURU (KKG) DI GUGUS KAWAN KECAMATAN BANGLI TAHUN 2018 - I Nyoman Wiranata (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2019)
One of the government agenda is to improve the quality of national education curriculum. The Centralistic of National curriculum system implementation has produced cognitive behaviors of students who are less flexible. According to the current 2013 curriculum, it requires new strategies, especially in learning activities. The learning approach which was previously dominated by the role of the teacher (teacher centered) was updated with a studentcentered learning system. One of this learning strategies are using the Pakem approach. By utilizing the school environment as a learning resource, the implementation standard of learning, the students will be able to develop creativity, motivation and participation in learning process. Furthermore, based on the results of the observation as a supervisors of Hinduism education, (PAH) teachers in the Cluster of Bangli district, are very rare and never used the school environment as a source of learning. The study was conducted to utilize the school environment as a learning resource and to find out the weaknesses and strengths of the (PAH) Teacher Working Group (KKG) discussion in improving teachers' ability. This study was a School Action Research which carried out in two cycles, where each cycle was carried in three meetings. The subjects of this study were (PAH) teachers in Cluster which 8 number of people. The data was collected by using the observation format, learning scenario assessment instruments and assessment instruments for learning implementation. Furthermore, the collected data is analyzed by using descriptive analysis. Based on the result of this study it can be found that, in the first cycle the average value obtained from the teacher's attitude to discuss the discussion was 79.38, while in the second cycle the average value obtained was 84.88. The average value obtained from the assessment of learning scenario in the first cycle is 78.75, while in the second cycle the average value obtained 82.50. The average value obtained from the assessment of learning implementation in the first cycle is 78.33, while in the second cycle the average value obtained 82.08. By looking at the average value obtained from the results of the analysis, it can be concluded that, from cycle I to cycle II, an increase in the average value obtained from each component is observed and assessed, which means that the guidance through the teacher working group discussion approach can improve the ability of teachers in using the school environment. Based on the result mentioned above, it is suggested to (PAH) teachers in Bangli Districts to optimize the use of the school environment as a learning resource by increasing the variety of learning methods in the preparation of learning scenarios and in the implementation of learning